Asian Learners’ Perception of Quality in Distance Education and Gender Differences - Jung, Insung (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
There have been few efforts to investigate the concept of quality from learners’ perspectives or to incorporate their needs and perceptions in quality standards in distance education. This is rather surprising, particularly in distance education contexts where the quality of the learning is not derived only from the products and services delivered to the learner but also from the knowledge, understanding, and relationships that are codeveloped by both teachers and learners during the teaching and learning processes. This study proposes and verifies a conceptual model of the 10 dimensions of quality in distance education from the learners’ perspectives and investigates gender differences in the perception of quality in distance education with 1,665 distance learners from 11 Asian countries and one territory. The results show that all 10 dimensions across supportive, pedagogical, and environmental domains in the model are important in judging quality in distance education. Also, gender differences are found in the perceived importance of 10 quality dimensions, barriers to DE, important supporters, and types of support received. The implications of these findings are discussed and suggestions for further research and development are offered.